KAJIAN PERAN ANGKAK PADA KUALITAS TEMPE KEDELAI-LAMTORO GUNG (Leucaena leucocephala) (Jurnal Teknologi Pangan, 2013)
In  general,  people  use  soy  as  an  ingredient  of  making tempeh,  tempeh  increased  demand resulted in a growing number of imported soybeans.The efforted can be done to overcome this is by replacing or mixing of raw materials (soybeans) with other materials. Substitute one ingredient is soy beans  lamtoro  stage.  Diversification  of  products  tempeh  can  be  done  by  adding  lamtoro  gung  and red  yeast  rice  in  soy  tempeh.  This  study  aims  to  determine  the  effect  of  the  proportion  of  soybean seeds:  lamtoro  gung  and  the  addition  of  red  yeast  rice  to  quality  tempe.  Research  using  Complete Randomized  Design  (CRD)  factorial  pattern  with  two  factors  and  two  replications,  the  proportion  of soybean Factor I: lamtoro gung 70%: 30%, 50%: 50%, 30%: 70%. Factor II, the addition of red yeast rice  1%,  2%,  3%.  The  results  showed  that  the  best  treatment  is  the  treatment  the  proportion  of soybean: lamtoro gung (70:30) and the addition of 1% red yeast rice is produced tempeh with criteria 1% addition of red yeast rice that has a water content of 62.42%, ash content 3.30%, levels 14.99% protein, fat  content  of  3.99%,  3178.41  ppm  phenol  content,  antioxidant  activity  of  59.47%,  texture (hardness) 0.241 mm / sec and the gr 72 favorite color, flavor 75, flavor 73, compactness 71 .Key words: soybean, lamtoro gung red yeast rice